MACRO-ACCOUNTING: EXPLORING THE INTERACTION OF INEQUALITY, SECTORAL EMPLOYMENT, AND ECONOMIC GROWTH ON POVERTY (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study investigates the impact of income distribution and macroeconomic dynamics on poverty in five major Asian countries, Bangladesh, India, Indonesia, the Philippines, and Vietnam, between 2010 and 2021. Using a panel data regression approach, the analysis incorporates key macro-accounting variables, including the Gini index, income shares, GDP growth, consumption growth, and employment structure. The study introduces the concept of idiosyncratic risk at the household level, operationalized through consumption volatility and income inequality, and tests whether consumption growth moderates the relationship between inequality and poverty. While individual variables were not statistically significant, primarily due to small sample size and data limitations, the overall model explains over 90% of the variance in poverty rates. The findings reveal that inclusive and stable consumption growth, structural labor shifts, and inequality mitigation are critical to effective poverty reduction. This research highlights the value of macro-accounting frameworks for integrated policy design and suggests future pathways for improving empirical rigor and policy relevance in development economics.
Keywords: Poverty; Inequality; Macro-accounting; Idiosyncratic Risk; Consumption Growth; Gini Index